822 CASES OF MALIGNANT BREAST NEOPLASIA FROM THE UBÁ BREAST INSTITUTE. - Moura, Jackson Roberto de; Moura Júnior, Jackson Roberto de; Moura, Jackline Zonta de; Teixeira, Áquilla Henrique Gonçalves; Moura, Jardel Antônio da Silva (Mastology, 2020)
Objective: To verify the profile of the presentation and the surgical treatment performed in a service in the state of Minas Gerais, Brazil. Methods: Descriptive prospective case series study, carried out based on cases handled by the same team from March 2001 to December 2019, archiving pre-defined information and analyzing data using the R and SPSS PC software. Results: 822 cases were diagnosed and treated at the service, with a mean age of 56.6 years + 14.1 (ranging from 24 to 96 years), with patients from 44 different cities, predominantly Ubá, Minas Gerais (31%). Infiltrating Ductal Carcinoma was the histopathological type of most cases (65%) with a mean tumor size of 21.8 mm + 20.8. The predominant immunohistochemical type was Luminal B HER negative (33%). Initial staging predominated, with 37% of patients in clinical stage IA. The surgical approach was conservative in most cases (73%), with sentinel lymph node surgery (183 cases) and oncoplasty surgery (278 cases). In the follow-up after treatment, we have 17% of the discharge after 10-year free survival, 15% of death, and 7% of metastatic disease in chemotherapy. Conclusion: There was a predominance of patients with initial tumors, which enabled a high rate of treatment with breast conservation and with a future expectation of reducing mortality from the disease.